AN INVESTIGATION OF THE PROCESS OF WRITING AN INTERNATIONAL JOURNAL ARTICLE OF FOUR POSTGRADUATE STUDENTS OF ENGLISH LANGUAGE EDUCATION PROGRAM IN INDONESIA - Geby Devtiana Maryono, - (2022)
This study aims to explore the writing process employed by English education postgraduate students in a university in Bandung who have succeeded in publishing academic research articles in international journals. The theoretical frameworks of this study are the synthesis of theories from writing process approach and genre approach. This study employed a qualitative approach with case study design involving four English education postgraduate students who have their publications in international journal as the participants. The participants were chosen after contacting the postgraduate students from various cohorts to ask about those who have successfully published journal articles in international journals. As a result, two master and doctoral students agreed to participate in this study. The data for this study were collected through document analysis and interview. The data from these resources were analyzed through thematic analysis to tease out the emerging themes by employing open coding and axial coding. The themes emerged from this study are writing stages, benefits of each stage, and challenges of each stage. The first theme of this study shows that students went through prewriting, drafting, revising, editing, and publishing with different activities in each stage for each student. All activities done in each stage are beneficial to journal article composition and manuscript quality. The benefits of the stages are thorough topic understanding, improvement of manuscript quality, and professional look of manuscript. However, each stage also has its own challenges such as personal reasons to spare time writing the manuscript, finding suitable references, and understanding reviewers' feedback. The results of this study are expected to bring enlightenment in the issue of writing process in a specific writing task, to give guidance for the students about effective writing process, and to initiate the release of a policy for the extensive writing program which focuses on preparing students for more effective writing process, especially journal article writing as one of academic writing tasks.